MANAQIBAN OF SHAIKH ABDUL QADIR AL-JAILANI TRADITION: Study of Living Hadith in Kunir Wonodadi Blitar East of Java - Noorhidayati, Salamah; Mahmud, Kharis (KALAM, 2018)
This article examines the meaning of tradition in Syaikh Abdul Qadir Jailani’s Manaqiban recitation in Kunir village, Wonodadi, Blitar.  This article is written based on the research using qualitative method and phenomenology approach. Data collected from observation, interviews, and document reviews are analysed using Karl Manheim’s theory of knowledge. This article demonstrates that, first, manaqiban tradition understood by the Kunir villagers as form of Islamic teaching guided by the Qur’an and the hadith and a medium for acquiring blessing from the Saint. Second, for the Kunir villagers, the manaqiban tradition has three meanings, i.e. objective meaning referring to a form of religious observance; expressive meaning referring to the motives jama’ah has in manaqiban participation; documentary meaning referring to the meaning of manaqiban as a means to preserve Islamic teaching and accommodate local culture in order to create religious and social life of society.